The two stages of Jinghao's "Truth" -- "Taking truth from things" （度物取真）and "Searching wonderful and creating Truth"（搜妙创真） (Journal of Global Arts Studies, 2023)
Background: Jing Hao was a famous theorist and painter in the Central Plains during the late Tang and Five Dynasties. He put forward "truth" in "Bi Fa Ji", and his art works also proved the practice of "truth" everywhere. So what is the "truth" proposed by Jing Hao? Objective: This paper mainly analyzes Jinghao's "truth" from the metaphysical level, because Jinghao's "truth" is established in the scope of life reflection, heart source experience and heaven and earth concept, which is a combination of physical and metaphysical. Only by thoroughly analyzing the metaphysical formation path of "truth" can we better understand that Jinghao's "truth" not only needs physical tools, but also needs metaphysical ways. Only by combining the instrument and Tao can we create the true scenery, mountains and rivers, and finally reach the ideal "truth" of Jinghao's art. Methods: Therefore, this paper mainly focuses on the text of "Bi Fa Ji" and discusses Jing Hao's "truth" from the two aspects of "taking truth from things" and "searching for beauty and creating truth" through literature research and other methods. Results: trying to analyze how the metaphysical level of "truth" is constructed in Jing Hao's art world. Conclusion: Through the study of the metaphysical "truth", it lays a solid foundation for the later forms.
Keywords: Jing Hao; "True"; Bi Fa Ji; Metaphysical